IMPLEMENTASI NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI - Tarom, Muhamad (LPPM UNSAP & FISIP UNSAP, 2024)
The lack of application of Pancasila values, especially among the current millennial generation, shows the weak implementation of Pancasila values in people's lives. This writing uses a literature study approach by utilizing facts and supporting sources, such as ebooks, articles and a number of related journals. The meaning of Pancasila, its application in everyday life, and examples of its application in various aspects of life are explained according to known facts. This article aims to study how humans organize their daily lives by applying Pancasila as a guide to life. It can also be a guide for the community on how to apply Pancasila values into everyday life and make people aware of the importance of Pancasila, so that it can also be a guide in implementing it in various aspects of life